Mga kagamitang panturo sa pinatnubayan tungo sa malayang pagsulat sa ikaapat na taon para sa mga estudyanteng Ilokano sa Cagayan - Mercado, Teresita P.; Mercado, Teresita P.
This seminar paper attempts to present exercises and samples of lesson plans in teaching guided to free writing for fourth year Ilokano students of Pilipino in Cagayan. Each exercise contains behavioral objectives that will develop the teacher's skill and ability to prepare instructional materials slanted towards the linguistic approach in teaching composition writing.